Obsession eaudiobook - Woods, Stuart (Teddy Fay, 2023)
Teddy Fay must put all his skills to the test in this electrifying new adventure in the New York Times bestselling series. While filming on location in scenic Santa Barbara, California, Peter Barrington and Ben Bacchetti look to expand Centurion Studios' business by making a deal with a young Croatian tech billionaire. But when the magnate’s wife is kidnapped, Teddy Fay is brought in to assess the threat and recover the young woman. As Teddy unravels the threads of her disappearance, he quickly comes to find an old vendetta seethes at the center, one that puts them all at risk. And danger is lurking even nearer to home as an obsessive fan with perilous intentions weasels his way onto the film set. It’s only Teddy who can stop him from getting too close for comfort.